Differential expression of urine-circulating micro-RNAs in Chlamydia trachomatis-induced recurrent spontaneous aborters. (November 2021) - Ray, Ankita; Bhati, Tanu; Arora, Renu; Pradhan, Dibyabhaba; Parvez, Suhel; Rastogi, Sangita
Abstract: Studies behind mechanisms of Chlamydia trachomatis -induced recurrent spontaneous abortion is still in its infancy. Possible strategy for preventing recurrent spontaneous abortion at molecular level is needed. Despite its multifactorial aetiology, Chlamydia trachomatis is important cause of RSA. However, mechanism leading to RSA in C. trachomatis -positive patients is not understood and novel strategies are needed. It is hypothesized that microRNAs play important role in RSA regulation during infection. Study aimed to elucidate expression/role of urine-circulating miRs-320b, 221-3p, 146b-5p, -16, -24, -559 in recurrent spontaneous aborters with C. trachomatis infection and to find their target genes by bioinformatic analysis. First-void urine was collected from 30 non-pregnant women with RSA (Group I) and 30 non-pregnant women with ≥2 successful deliveries (Group II; Controls) attending Department of Obstetrics and Gynaecology, Vardhman Mahavir Medical College, Safdarjung hospital, New Delhi (India). PCR was performed to detect C. trachomatis . Expression of miRNAs was studied by quantitative real-time PCR while target genes/functional annotations were predicted by GO/KEGG databases. Data was statistically evaluated. 05 RSA patients were C. trachomatis -positive. Group I was subdivided into Group Ia ( C. trachomatis -positive RSA; n = 5) and Group Ib ( C. trachomatis -negative RSA; internal controls). miR-320b, -221-3p, −146b-5p, −16, −24 were significantly upregulated (miR-16 showed maximum 4.3 fold-change) while miR-559 was downregulated (0.5 fold-change) in Group Ia versus controls ('p'<0.001). Bioinformatic analysis revealed that target genes of miRNAs in RSA are involved in apoptosis and AMPK signalling pathways. Results showed differential expression of miRNAs implyingmiR-16 and miR-559 as potential biomarkers of RSA in infected women. Furthermore, network of genes of differentially expressed miRNAs regulates RSA by targeting gene function in apoptosis, cell adhesion and angiogenesis. Highlights: Micro-RNAs play important role in regulation of recurrent spontaneous abortion (RSA) during Chlamydia trachomatis infection. miR-320b, -221-3p, −146b-5p, −16, −24 were upregulated; however, miR-559 was downregulated in infected aborters. miR-16 showed maximum 4.3 fold-change while miR-559 showed 0.5 fold-change ('p' < 0.001) in infected patients. Differential expression of miRNAs revealed miR-16 and miR-559 as potential biomarkers of RSA in Chlamydia -infected women. Bioinformatic analysis revealed that target genes of miRNAs in RSA are involved in apoptosis and AMPK signalling pathways.